A Prospective Controlled Trial Comparing Weekly Self-testing and Self-dosing with the Standard Management of Patients on Stable Oral Anticoagulation - Watzke, H. H.; Forberg, E.; Svolba, G.; Jimenez-Boj, E.; Krinninger, B. (Thrombosis and Haemostasis, 2000)
Oral anticoagulant therapy requires frequent laboratory controls of its intensity to assure therapeutic efficacy and to prevent potentially life threatening adverse events. It is generally assumed, that increasing the frequency of testing would lead to a better control of anticoagulation. We tested this hypothesis in a prospective controlled trial comparing weekly self-testing and self-dosing (self management) with the standard-management of these patients in an anticoagulation clinic. Only patients with stable anticoagulation were included into the study. We recorded 2733 weekly determinations of the intensity of anticoagulation (INR) in 49 patients on self-testing and self-dosing and 539 determinations of the INR in 53 patients on standard-management. Two intensities of anticoagulation were used in each group: a target INR of 3.5 for patients with artificial heart valves (target range: 2.5–4.5) and a target INR 2.5 (target range: 2.0–3.0) for patients with atrial fibrillation or venous thromboembolism. The deviation from the target INR, the fraction of INR determinations within the preset therapeutic range and the difference between the target INR and the actually achieved mean INR were the three major endpoints of the study. The mean deviation from the target INR was smaller in the groups of patients on self–management compared to the patients on standard-management. Individual deviations were significantly (p <0.0001) dependent on the type of management in interaction with the treatment intensity in a general linear model. Patients on weekly self-testing and self-dosing had more INR values within the therapeutic range than patients on standard-management (86.2% vs. 80.1% at INR range 2.5–4.5; 82.2 vs. 68.9 at INR range 2.0–3.0). The achieved mean INR was almost identical with the target INR in the patients on self-management but was significantly (p <0.005) below the target INR in the high intensity anticoagulation group on standard-management (target INR:3.5; achieved mean INR: 3.19; CI 0.95: 3.05–3.34).Our data show, that weekly self-testing and self-dosing leads to a better control of anticoagulation than standard treatment in an anticoagulation clinic.The technical equipment used for self testing in this study was provided by Roche Diagnostics, Austria
Keywords: Oral anticoagulation; artificial heart valves; venous thrombosis; self-management